2019
DOI: 10.1007/s13197-019-04124-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen sources and neutralizing agents on D-lactic acid production from Kodo millet bran hydrolysate: comparative study and kinetic analysis

Abstract: D-lactic acid (DLA) serves as a key monomer enhancing both the mechanical and thermal properties of Poly(lactic) acid films and coatings, extensively used in the food packaging industry. Economically viable production of optically pure DLA by Lactobacillus delbrueckii NBRC3202 was achieved using a low-cost carbon source, Kodo millet bran residue hydrolysate (KMBRH) and nitrogen source (casein enzyme hydrolysate (CEH) resulting in a high DLA yield of 0.99 g g -1 and KMBRH conversion to final product (95.3%). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The logistic equation represents classic kinetic model techniques during batch cultivations that describe biomass development. A logistic model considering only cell growth variables and therefore independent of the substrate was applied to predict the biomass and is given in Equation (3) ( Balakrishnan et al, 2020 ). …”
Section: Methodsmentioning
confidence: 99%
“…The logistic equation represents classic kinetic model techniques during batch cultivations that describe biomass development. A logistic model considering only cell growth variables and therefore independent of the substrate was applied to predict the biomass and is given in Equation (3) ( Balakrishnan et al, 2020 ). …”
Section: Methodsmentioning
confidence: 99%
“…It is very likely that if the fermentation had not been interrupted in 48 h, greater L (+) lactic acid production could have been obtained with this fermentation, as production with exponential feeding was only 112.71 g/L L (+) lactic acid in 48 h when pH was controlled by NaOH 10 N and CaCO 3 (Figure 8c). Balakrishnan et al [21] found that although lactic acid production and yield was better when using CaCO 3 to control pH compared to NaHCO 3 , the latter is more indicated because at lower cost and e solubility of sodium lactate is higher which led to an easier separation of LA.…”
Section: Fed Batchmentioning
confidence: 99%
“…gardening residues [17], crystal sugar [18,19], municipal biopulp [20], Kodo millet bran hydrolysate [21,22], bakery waste and lucerne green juice [23], sugarcane bagasse [24][25][26] and sugar beet pulp [27].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the recent literature, López-Gómez et al [22] produced 61.1 g/L of l-lactic acid from hydrolyzed municipal solid waste on a batch mode, noticing a high positive impact of yeast extract addition on the media. Balakrishnan et al [23] produced 45.08 g/L of d-lactic acid from hydrolyzed millet bran residue and hydrolyzed casein, with a productivity of 0.45 g L −1 h −1 . Tian et al [24] produced 114.6 g/L of lactic acid from purified sweet sorghum juice and soybean hydrolysate with a productivity of 2.61 g L −1 h −1 on a simple batch mode.…”
Section: Lactic Acid Fermentationmentioning
confidence: 99%